Écologie et urbanisme : comment les experts du vivant peuvent-ils contribuer à la conception du cadre urbain ? - Robin Chalot (VertigO)
Since more than fifty years, concern about biodiversity loss has kept on growing. It gave birth to policies and legal rules aiming to decrease the impact of urbanization. It goes with a popular request for restoring some Nature in cities, expressed through a range of citizen ventures redefining urban space. There are still scientific questions as to urban ecosystems composition, their interactions with artificial structures and their part in biosphere. However, many studies show beneficial effects of wildlife on urban landscapes, for example facing global warming. Practical experiments have been trying to reconcile city and nature, but their actual benefits for biodiversity are debated. Some might be irrelevant regarding ecosystems functioning, especially due to urban planners' lack of ecological training. This article ponders how urban planners may benefit from welcoming ecological skills in their team. Having such knowledge in house would facilitate the reciprocal understanding between fields, the efficient integration of wildlife in urban planning projects and an exhaustive consideration of the components of urban systems. Handling each project individually is a key feature for a qualitative approach, well-suited to modern stakes. Cross-training between ecology and urban planning might promote the rise of new professions at the confluence of these two fields.